TREATMENT WITH FLT3 INHIBITOR IN PATIENTS WITH FLT3-MUTATED AML IS ASSOCIATED WITH DEVELOPMENT OF SECONDARY FLT3-TKD MUTATIONS - Alvarado, Yesid (2014)
BACKGROUND: FLT3-internal tandem duplication (ITD) mutations are found in approximately 30% of AML patients. FLT3 inhibitors have shown clinical activity in AML with FLT3-ITD but responses are usually short lived. METHODS: We reviewed 69 FLT3 mutated AML patients, treated with different FLT3 inhibitors to analyze emergence of new mutations. RESULTS: At baseline 87% of patients had an ITD mutation, 7% had a D835/I836 mutation and 6% had combined ITD and D835/I836 mutations. Responses occurred in 32% of patients, all with FLT3-ITD; none of the patients with D835/I836 or ITD+D835/I836 responded. Mutational assessment at the time FLT3 inhibitor discontinuation showed that 68% of patients were unchanged, 10% had become undetectable, and 22% of patients progressed from a single ITD to have combined ITD+D835/I836 mutations. In those patients with unchanged FLT3 mutation at progression the median survival was 5 months, while in those with undetectable and with combined ITD-D835/I836 mutations the median survival was 7 months respectively. CONCLUSION: This data confirm in vitro observations that a secondary TKD mutation may arise after the use of FLT3 inhibitors in patients with single FLT3-ITD mutated AML, a phenomenon that is associated with resistance and a poor prognosis.